Verubulin (Azixa) Analogues with Increased Saturation: Synthesis, SAR and Encapsulation in Biocompatible Nanocontainers Based on Ca2+ or Mg2+ Cross-Linked Alginate - Kseniya N. Sedenkova; Denis N. Leschukov; Yuri K. Grishin; Nikolay A. Zefirov; Yulia A. Gracheva; Dmitry A. Skvortsov; Yanislav S. Hrytseniuk; Lilja A. Vasilyeva; Elena A. Spirkova; Pavel N. Shevtsov; Elena F. Shevtsova; Alina R. Lukmanova; et al. (MDPI AG, 2023)
Tubulin-targeting agents attract undiminished attention as promising compounds for the design of anti-cancer drugs. Verubulin is a potent tubulin polymerization inhibitor, binding to colchicine-binding sites. In the present work, a series of verubulin analogues containing a cyclohexane or cycloheptane ring 1,2-annulated with pyrimidine moiety and various substituents in positions 2 and 4 of pyrimidine were obtained and their cytotoxicity towards cancer and non-cancerous cell lines was estimated. The investigated compounds revealed activity against various cancer cell lines with IC50 down to 1-4 nM. According to fluorescent microscopy data, compounds that showed cytotoxicity in the MTT test disrupt the normal cytoskeleton of the cell in a pattern similar to that for combretastatin A-4. The hit compound (N-(4-methoxyphenyl)-N,2-dimethyl-5,6,7,8-tetrahydroquinazolin-4-amine) was encapsulated in biocompatible nanocontainers based on Ca2+ or Mg2+ cross-linked alginate and it was demonstrated that its cytotoxic activity was preserved after encapsulation.